Carotid Artery Stenosis as a Risk Factor for Crescendo Transient Ischemic Attack: Case Report - Amry, Carissa Maharani; Imran, Yudhisman; Rahmansyah, Mulia; Rachmiyani, Irmiya; Khusfiani, Triasti (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2025)
Background A Transient Ischemic Attack (TIA) is an indicator of ischemic stroke. When the frequency, duration, and severity of TIAs increase, they are known as a Crescendo Transient Ischemic Attack (cTIA). Several risk factors, including carotid artery stenosis, can contribute to cTIA. Case Description A 49-year-old man presented to the Emergency Department (ED) after being referred from another hospital, complaining of sudden weakness on the left side of his body that started three days ago. The weakness on his left side was noted to be intermittent. The patient initially experienced sudden weakness on the left side of his body five days before his hospital admission at 2:00 PM, after which his condition improved. That evening, at 8:00 PM, the patient again experienced sudden weakness on the left side, but it improved to normal afterward. Four days before admission, at 12:00 PM, the patient experienced weakness on the left side along with slurred speech, which also improved. Before being referred, the patient underwent a non-contrast head computed tomography (NCCT), revealing no bleeding. The neurological physical examination was within normal limits. The patient was hospitalized and received dual antiplatelet therapy (Aspilet and Clopidogrel), Ranitidine, Citicoline, Mecobalamin, and Atorvastatin. He was discharged on the second day, with no neurological deficits observed during treatment. The patient was evaluated at the neurology clinic and underwent CT angiography of the carotid arteries, revealing moderate stenosis (50 - 69% NASCET Scale stenosis) in the right internal carotid artery and mild stenosis (<50% NASCET scale stenosis) in the left internal carotid artery. Conclusions Crescendo Transient Ischemic Attack (cTIA) is an important indicator of ischemic stroke requiring hospitalization. In cTIA, a supporting examination is needed, typically computed tomography angiography (CTA). This imaging technique has high sensitivity for detecting intracranial stenosis and occlusion, which are significant risk factors for recurrent TIA. In high-risk TIA patients, DAPT (aspirin and clopidogrel) should be started early to reduce the risk of recurrent ischemic stroke. Keywords: Transient Ischemic Attack, Crescendo Transient Ischemic Attack, computed tomography angiography